The effect of different solvents on the morphology and performance of the ZIF-8 modified PVDF ultrafiltration membranes - Karimi, Atefeh; Khataee, Alireza; Vatanpour, Vahid; Safarpour, Mahdie (Elsevier, 2020)
In this research, the PVDF-based nanocomposite membranes modified with ZIF-8 nanocrystals were prepared with various casting solvents containing, DMSO, NMP, DMF and DMAc. The SEM, EDX and AFM analyses were applied to study morphology, distribution of the ZIF-8 in the matrix of the polymer, and surface roughness characteristic of the mixed matrix membranes, respectively. The impact of the solvent type on the structure and filtration efficiency of the resulting membranes was studied by considering the thermodynamic and kinetic factors of the membrane formation. A significant correlation was found between the diffusion rates of the solvent/non-solvent and the sub-layer structure of the membranes. Membranes cast with DMAc and DMF solvents (with relatively high diffusion rates) presented a bigger number of the finger-like cavities with a smaller size compared with membranes prepared by DMSO and NMP with lower diffusion rates. Blending of the ZIF-8 nanoparticles within the membrane matrix with a proper concentration (up to 0.2 wt%) resulted in an increase in the size of the finger-like cavities, lead to increase in the permeability of the resulting membranes. With increasing the ZIF-8 content to 0.5 and 1 wt%, the finger-like pores turned to sponge-like pores. The pure water permeation of the unmodified membranes cast with DMSO, NMP, DMAc and DMF was 258.64, 179.52 156.65 and 10.52 L/m(2)h, respectively, which was in good agreement with the observed trend for porosity and surface hydrophilicity of the membranes.
Keywords: Solvent effect; Nanocomposite; Diffusion; Thermodynamic; ZIF-8 nanoparticles